2017
DOI: 10.1071/mf15314
|View full text |Cite
|
Sign up to set email alerts
|

Coral bleaching in turbid waters of north-western Australia

Abstract: We report severe bleaching in a turbid water coral community in north-western Australia. Towed still imagery was used for a benthic survey near Onslow in March 2013 to assess thermal stress in hard and soft corals, finding 51–68% of all corals fully bleached in 10–15-m water depth. Tabulate or foliaceous Turbinaria was the locally most abundant hard coral (46%), followed by massives such as faviids and poritids (25%) and encrusting coral (12%), thus over 80% of the local corals could be considered to be bleach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
3
34
1
Order By: Relevance
“…Previous studies have demonstrated positive relationships between live coral cover and the abundance and diversity of fish assemblages (Carpenter et al 1981;Connell & Kingsford 1998;Komyakova, Munday & Jones 2013). However, in the current study, the per cent cover of (live) hard and soft corals was low (~8% combined) compared to dead corals (~25%) possibly due to a bleaching event in March 2013 (Lafratta et al 2016) (Fig. S6); hence, the observed relationships between fish assemblages and dead coral cover (as also indicated by macroalgae) were stronger.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have demonstrated positive relationships between live coral cover and the abundance and diversity of fish assemblages (Carpenter et al 1981;Connell & Kingsford 1998;Komyakova, Munday & Jones 2013). However, in the current study, the per cent cover of (live) hard and soft corals was low (~8% combined) compared to dead corals (~25%) possibly due to a bleaching event in March 2013 (Lafratta et al 2016) (Fig. S6); hence, the observed relationships between fish assemblages and dead coral cover (as also indicated by macroalgae) were stronger.…”
Section: Discussioncontrasting
confidence: 68%
“…However, in the current study, the per cent cover of (live) hard and soft corals was low (~8% combined) compared to dead corals (~25%) possibly due to a bleaching event in March 2013 (Lafratta et al . ) (Fig. S6); hence, the observed relationships between fish assemblages and dead coral cover (as also indicated by macroalgae) were stronger.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, in the last two decades, abnormally intense warm‐water events have affected both high and low‐latitude reefs in the SEIO, of which the 2011 heatwave was the most severe (Abdo, Bellchambers, & Evans, ; Depczynski et al., ; Feng, McPhaden, Xie, & Hafner, ; Hobbs & McDonald, ; Moore et al., ; Wernberg et al., ; Zhang, Feng, Hendon, Hobday, & Zinke, ; Zinke et al., ). Moreover, since 2011, anomalously warm SSTs have caused persistent summer heat stress and severe coral bleaching at many SEIO reefs (Caputi, Jackson, & Pearce, ; Feng et al., ; Lafratta, Fromont, Speare, & Schönberg, ). These stresses are likely to interact with aspects of background temperature variation to produce changes in coral communities that may not be linearly related to historical temperature variation.…”
Section: Discussionmentioning
confidence: 99%
“…Record temperatures in early 2016 caused unprecedented levels of coral bleaching and mortality [3][4][5]. Despite these widespread perturbations on coral reefs, research conducted by Cinner et al [6] has revealed many 'bright spot' and 'dark spot' reefs that, for unexplained reasons, are more or less resilient to climate change.…”
Section: Introductionmentioning
confidence: 99%